2004
DOI: 10.1159/000076390
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Pregnancy-Associated Plasma Protein-A to Renal Function and Dialysis Modalities

Abstract: Background: The aim of the study was to determine pregnancy-associated plasma protein-A (PAPP-A), which was recently described as a new marker of cardiovascular events, in patients with chronic renal insufficiency/failure and to find out its relationship to renal function and to prominent markers of oxidative stress (advanced oxidation protein products – AOPP) and inflammation (C-reactive protein – CRP). Methods: The studied group consisted of 36 chronic hemodialysis patients (HD), 10 patients treated with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
(56 reference statements)
6
25
0
Order By: Relevance
“…PAPP-A has been demonstrated also in eroded and ruptured atherosclerotic plaques, and its serum levels were increased in patients with acute coronary syndromes [5] . It is elevated also in chronic hemodialysis patients [6,7] and might be associated with the mortality of these patients, as shown in our preliminary study [8] . Additionally, the pre-TX serum concentration of PAPP-A was recently demonstrated as a predictor of post-TX cardiovascular events and chronic allograft nephropathy [9] .…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…PAPP-A has been demonstrated also in eroded and ruptured atherosclerotic plaques, and its serum levels were increased in patients with acute coronary syndromes [5] . It is elevated also in chronic hemodialysis patients [6,7] and might be associated with the mortality of these patients, as shown in our preliminary study [8] . Additionally, the pre-TX serum concentration of PAPP-A was recently demonstrated as a predictor of post-TX cardiovascular events and chronic allograft nephropathy [9] .…”
Section: Introductionsupporting
confidence: 68%
“…PAPP-A is linked to the inflammatory process and vice versa, and this relationship can also be observed in serum. A significant correlation was found between PAPP-A and Creactive protein in patients with acute coronary syndromes [5] as well as in hemodialysis patients, in whom PAPP-A was also associated with advanced oxidation protein products [7] , markers of both inflammation and oxidative stress. Additionally, herein we showed a possible association of PAPP-A serum levels with intragraft interstitial inflammation and vascular intimal thickening.…”
Section: Discussionmentioning
confidence: 91%
“…In a preliminary study, the release patterns of PAPP-A were highly variable, increasing early at 2 h after admission or late at 30 h after the onset of chest pain (54 ). Because preliminary findings showed that serum PAPP-A concentrations sensitively reflect changes in renal function, at least in dialyzed patients, and correlate with serum creatinine, the possible dependence of PAPP-A concentrations on renal function should be clarified (55 ).…”
Section: Pregnancy-associated Plasma Protein Amentioning
confidence: 94%
“…In 2003, we fi rst described elevation of PAPP-A in patients with end-stage renal disease treated with hemodialysis (8) , and subsequently its relationship to renal function (9) and its possible prognostic role in long-term hemodialysis patients (10) . Elevation of PAPP-A measured by a different method with lower reference range was also confi rmed by Coskun et al (11) .…”
Section: History Of Papp-a In Laboratory Medicinementioning
confidence: 99%
“…PAPP-A is signifi cantly elevated mainly in patients with end-stage renal disease with lower levels in patients treated with peritoneal dialysis than in patients treated with hemodialysis (9) . PAPP-A is detectable also in spent peritoneal dialysate but these concentrations are not related to serum levels.…”
Section: Clinical and Laboratory Studies In Patients With Kidney Disementioning
confidence: 99%